Study of Functional Property of Bread Based on Buckwheat and Green Tea - Bhattarai, Shraddha; Ojha, Pravin; Rai, Krishna Prasad (Journal of Food Science and Technology Nepal, 2014)
A study was conducted to formulate and observe the functional properties of bread based on buckwheat and green tea. The physiochemical and functional properties of the raw materials used and that of the best sample were also analyzed. The TPC in BWF and GT were found to be 51 GAE and 95 GAE respectively. In other hand, antioxidant activity was found to be 7.1% and 39.2% respectively. From the sensory evaluation, the sample with 60:40 ratio of BWF: WF and 3% GTB incorporated was found to be superior. Furthermore, iron, calcium, tannin content, total polyphenol content and antioxidant activity of the best product were found to be 3.133 mg /100g, 315.56mg/100g, 0.0000084%, 71GAE and 5.6% respectively. Additionally, a comparative proximate composition analysis of the best sample and market product was analyzed and the result showed the protein content of the lab sample was about 3 times more than that of the market product. Therefore, the lab prepared bread was found to be highly nutritious with functional characteristics with acceptable sensory qualities and shelf-life. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10610 J. Food Sci. Technol. Nepal, Vol. 7 (70-75), 2012